Milk Yield and its Composition of Crossbred Dairy Cows Fed Different Types of Grasses - Islam, Md. Asraful; Alam, Md. Jahangir; Kabir, Md. Enayet; Hossain, SM Jahangir; Yasmin, Farzana (European Journal of Applied Sciences, 2021)
The present study was undertaken to evaluate the effects of different grasses in diets for lactating cows and their implications on milk production and itscomposition. Twenty lactating crossbreed (♂HF x ♀Local) cows at about same age,lactation stage and production level were divided into four groups having five cows in each group. Four different grasses like German, Para, Napier and Maize as green fodder were randomly assigned to four groups. Grasses were supplied adlibitum but the concentrate feed mixture were offered @1kg/2.5 litres of milk production.The feeding trial lasted for 35 days, of which 7 days were adjustment period. Results showed that average milk yield was significantly (p<0.05) higher (13.14 ±0.99 l/d)in Maize grass fed group than others. There were no significant differences on specific gravity and protein content of milk in different grass fed groups of cows.Fat and solids-not-fat content were also significantly (p<0.05) higher in Maize grass fed group than others.Lactose and ash content of milk differed significantly (p<0.05) among the cows fed different experimental diets. However, the highest lactose percent (4.86±0.09) was recorded in Para grass fed group but the highest ash percent (0.99±0.05) was recorded in Maize grass fed group.Therefore, it may be concluded that the cultivation of Maize grass should be encouraged for feeding dairy cows throughout the countryfor increased and quality milk production.